Formal Solutions of Certain Dual and Triple Series Involving the Fox H-Functions - Ansari, Alireza (Journal of Informatics and Mathematical Sciences, 2011)
It this paper we show how certain classes of dual (triple) series equations involving the Fox H-functions can be reduced to some dual (triple) integral equations involving the Fox H-functions. Also, using the Erdelyi-Kober operators of fractional integration exact solutions of these dual (triple) integral equations are obtained.